Patient-Reported Experiences after Acute Kidney Injury across Multiple Health-Related Quality-of-Life Domains. Issue 3 (31st March 2022) - Switzer, Galen E.; Puttarajappa, Chethan M.; Kane-Gill, Sandra L.; Fried, Linda F.; Abebe, Kaleab Z.; Kellum, John A.; Jhamb, Manisha; Bruce, Jessica G.; Kuniyil, Vidya; Conway, Paul T.; Knight, Richard; Murphy, John; et al.
Key Points: Eighty-four percent of respondents reported that the AKI episode was very/extremely impactful on physical/emotional health. Fifty-seven percent reported being very/extremely concerned about AKI effects on work, and 67% were concerned about AKI effects on family. Future research should incorporate more comprehensive HRQoL measures and providers should give more information to patients about AKI. Visual Abstract: Abstract : Background: Investigations of health-related quality of life (HRQoL) in AKI have been limited in number, size, and domains assessed. We surveyed AKI survivors to describe the range of HRQoL AKI-related experiences and examined potential differences in AKI effects by sex and age at AKI episode. Methods: AKI survivors among American Association of Kidney Patients completed an anonymous online survey in September 2020. We assessed: ( 1 ) sociodemographic characteristics; ( 2 ) effects of AKI—physical, emotional, social; and ( 3 ) perceptions about interactions with health care providers using quantitative and qualitative items. Results: Respondents were 124 adult AKI survivors. Eighty-four percent reported that the AKI episode was very/extremely impactful on physical/emotional health. Fifty-seven percent reported being very/extremely concerned about AKI effects on work, and 67% were concerned about AKI effects on family. Only 52% of respondents rated medical team communication as very/extremely good. Individuals aged 22–65 years at AKI episode were more likely than younger/older counterparts to rate the AKI episode as highly impactful overall (90% versus 63% younger and 75% older individuals; P =0.04), more impactful on family (78% versus 50% and 46%; P =0.008), and more impactful on work (74% versus 38% and 10%; P <0.001). Limitations of this work include convenience sampling, retrospective data collection, and unknown AKI severity. Conclusions: These findings are a critical step forward in understanding the range of AKI experiences/consequences. Future research should incorporate more comprehensive HRQoL measures, and health care professionals should consider providing more information in their patient communication about AKI and follow-up.